If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -5 = 7x + -3 Reorder the terms: -5 + 4x = 7x + -3 Reorder the terms: -5 + 4x = -3 + 7x Solving -5 + 4x = -3 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -5 + 4x + -7x = -3 + 7x + -7x Combine like terms: 4x + -7x = -3x -5 + -3x = -3 + 7x + -7x Combine like terms: 7x + -7x = 0 -5 + -3x = -3 + 0 -5 + -3x = -3 Add '5' to each side of the equation. -5 + 5 + -3x = -3 + 5 Combine like terms: -5 + 5 = 0 0 + -3x = -3 + 5 -3x = -3 + 5 Combine like terms: -3 + 5 = 2 -3x = 2 Divide each side by '-3'. x = -0.6666666667 Simplifying x = -0.6666666667
| -(6v-2x-1)= | | -2-3-1= | | 270=0.5x^2+36x-40 | | 5-4-4= | | (2x+3)(x-6)-(5x+3)(3x+4)= | | 9r^2-5=76 | | ×/5=7.5 | | 4y+12=7y+36 | | 5m+4=3m+16 | | x^2-2x+2y^2=8 | | 100-50/10*5 | | -23=6r+16 | | 8-6-2= | | (3x-30)(3x+3)-(2x-1)=0 | | y^2-26y+45=0 | | 8m+5=5m+15 | | 11-2x=-x-3 | | -23=6r+12 | | 18r+4= | | -23=16r-5 | | 3x^2+2x-x=0 | | 5x+3=37x | | 54=8g+10-4(3g+12) | | 2(2x+40)=180 | | 54=8g+12-4(3g+12) | | 1x+5=10x | | 12-2y=y-6+3y | | 5(9x+13)=7(4x+10) | | -35+7+12-18-1-16= | | 2(6x+14)=7(8x+12) | | 2(x+8)=5(x+11) | | 16=3x-X |